Dispelling misconceptions in the management of familial adenomatous polyposis. Issue 6 (7th March 2017) - Chittleborough, Timothy J.; Warrier, Satish K.; Heriot, Alexander G.; Kalady, Matthew; Church, James
Abstract : Patients with familial adenomatous polyposis require surgical intervention at some point in their lives. The diagnosis is often apparent from their phenotype and family history, however, this is not always the case. Many factors can influence the surgical strategy although the polyposis burden and distribution remain the main consideration. While prophylactic removal of the rectum and colon is often required, sparing the rectum at the index surgery is safe in select patients. This article aims to dispel misconceptions in the diagnosis and treatment of patients with familial adenomatous polyposis.